Positron transport and acceleration in beam-driven plasma wakefield accelerators using plasma columns - S. Diederichs; T. J. Mehrling; C. Benedetti; C. B. Schroeder; A. Knetsch; E. Esarey; J. Osterhoff (Physical Review Accelerators and Beams, 2019)
A finite radius plasma is proposed to generate wakefields that can focus and accelerate positron beams in a plasma wakefield accelerator. The finite radius plasma reduces the restoring force acting on the plasma electrons forming the plasma wakefield, resulting in an elongation of the on-axis return point of the electrons and, hence, creating a long, high-density electron filament. This results in a region with accelerating and focusing fields for positrons, allowing for the acceleration and quality-preserving transport of high-charge positron beams.